Chalak bandar aur digar kahaniyan: bacho ke liye dilchasp sabaq aamoze kahaniyan (Children Publication Lahore, 2009)
A story featuring a clever monkey. It might involve a humorous tale, a problem-solving challenge, or a moral lesson about the importance of intelligence and adaptability.